User Experience Design (UXD): a survey of user interface development practices in Malaysia - Hussein, Idyawati; Mahmud, Murni; Md. Tap, Abu Osman (2012)
Despite the growing interest on user experience (UX) in the field of Human Computer Interaction (HCI) in other countries, little is known on how the UX approach is applied in the development of interfaces in Malaysia. An online questionnaire is distributed to the Information Technology (IT) development practitioners to identify what is the product/system development process in-practice and whether User Experience Design (UXD) is incorporated into that process. Majority of the respondents in this study claimed to embed UXD in the development life cycle. The result shows 75 percent of the respondents received formal education in HCI. However, when asked about difficulties to practice HCI/usability/UX, the respondents revealed a concerned to the increase of development time and declared to have lack of understanding to apply the terms. While current ongoing projects are mostly Web-based development, the highest rank of methodology in-use is rated as waterfall model. For this reason, the result of the study must be interpreted with caution. Further investigation should be conducted in practice using complimentary data collection methods such as interviews and end product evaluations. This study is an important empirical basis for many HCI practitioners who struggle to introduce HCI/usability/UX into the development process practices in Malaysia.